Impact of gender and mother education status on the immunization status of children in rural areas of Bijapur district, Karnataka, India - KJ, Shashank; MM, Angadi (International Journal Of Community Medicine And Public Health, 2017)
Background: Every child has the right to know and be cared for by his or her parents. The responsibility for the child’s well-being relies on both parents and the society. Since the ancient times, it is the gender that determines the position of a child in the Indian society. Gender is a common term whereas gender discrimination is meant for women, because females are more often the victims. Objectives of the study were to assess the impact of gender and mother education status on the immunization status of children in the rural areas of Bijapur district. Methods:A community based cross-sectional study was conducted in the rural areas of Bijapur district from the 1st December 2013 to 30th November 2014. A total of 207 children in the age group of 12-23 months from the villages across the district were included in the study as per the immunization coverage guidelines. The data was collected in pretested, semi-structured questionnaire and analyzed using SPSS version-21. Results:Overall 63.3% (68.8% male & 57.2% female) of children was fully immunized and the association between male and female was not statistically significant. The dropout rate for all the individual vaccines was high in the female children. Mother’s education had significant difference for getting male children fully immunized. The prevalence of gender bias among fully immunized children was 11.6% favoring towards the male children. Conclusions:Though the vaccination coverage of Bijapur district has improved over the years, the coverage is still lagging behind the state average as well as universal immunization programme target of 85% coverage. Gender of the child is one of the factors for the overall lesser coverage of immunization as more number of males was fully immunized than female children.